Pemberdayaan Peladang dalam Peningkatan Kompetensi dan Strategi Bisnis di Kawasan Seri Pulau, Penang, Malaysia - Risna, Meilia; Zuhriyah, Nur Azizah; Khulsum, Umi; Utami, Pertiwi; Basrowi; Md. Yusoff, Mohd Sukor bin Md. Yusoff; Nabela, Erick (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
The partners in this international community service program are representatives of farmers who are members of the Regional Farmers Association (PPK) Seri Pulau Pinang, Malaysia. The issues that partners have identified as requiring attention are as follows: (1) There is a lack of understanding among partners of how to improve existing competencies in order to develop a business; (2) There are no business strategy seminars conducted by international universities with the specific aim of empowering farmers; (3) There is no forum for discussion between academics and business actors. The aforementioned partner problem was addressed through the implementation of three proposed solutions, namely: (1) the organization of high-quality competency improvement seminars for farmers; (2) the organization of an international community service seminar for farmers in collaboration with PPK, UiTM Cawangan Pulau Penang, and 12 Indonesian universities that are members of the ASEAN Academic Association; and (3) the establishment of discussion forums at PPK Seri Pulau Penang and several business centers for farmers.